Critical Synthesis Package: Jefferson Scale of Physician Lifelong Learning (JeffSPLL) - Malorie Novak (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health science education of the both the Jefferson Scale of Physician Lifelong Learning (JeffSPLL) and the Jefferson Scale of Physician Lifelong Learning-Medical Students (JeffSPLL-MS), and (2) a copy of the JeffSPLL, JeffSPLL-MS, and the scoring instructions developed by Mohammadreza Hojat, PhD. The JeffSPLL and JeffSPLL-MS are 14-item, easy to administer, self-reported instruments that measure orientations and attitudes towards lifelong learning. The measures contain a validated 3-factor structure consisting of: Learning Beliefs and Motivation, Attention to Learning Opportunities, and Technical Skills in Seeking Information. As with any self-reported instrument, there is potential for social desirability response bias by respondents. However, using electronic databases, the authors confirmed the respondents' self-reported publication data and concluded that the internal validity of the JeffSPLL was unlikely to be distorted by such bias. In addition, the respondents used the full range of responses for the items on the JeffSPLL and JeffSPLL-MS. It should be noted that because the concept of lifelong learning is multifaceted, the three-factor structure may not capture all of its dimensions.